2018
DOI: 10.5761/atcs.cr.17-00072
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Kinked Stent Graft Limb Due to Severe Angulated Proximal Neck during Endovascular Repair for Abdominal Aortic Aneurysm

Abstract: Although the technology of endovascular aortic repair (EVAR) for abdominal aortic aneurysm (AAA) is evolving that make it appealing for challenging anatomy, proximal aortic neck morphology, especially severe angulation, is still one of the most determinants for a successful procedure. We describe a patient of AAA with severely angulated proximal neck, in whom kinked stent graft limb occurred against severe angulation of proximal neck. Then, we suggested how to prevent this complication in the second patient. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A severely tortuous and angulated aorta and iliac arteries can cause the stent graft to improperly adhere to the vessel walls. However, Oh et al 8 demonstrated that deploying stent graft limbs extensively above or below severely angulated vessels could prevent kinking of the stent graft.…”
Section: Discussionmentioning
confidence: 99%
“…A severely tortuous and angulated aorta and iliac arteries can cause the stent graft to improperly adhere to the vessel walls. However, Oh et al 8 demonstrated that deploying stent graft limbs extensively above or below severely angulated vessels could prevent kinking of the stent graft.…”
Section: Discussionmentioning
confidence: 99%
“…Device kinking may occur in 2–4% of patients, due to size reduction in the residual aneurysm sac over time, severe proximal aortic neck angulation and a narrow diameter of the distal aortic neck [ 3 , 49 , 50 ]. Device kinking (Fig.…”
Section: Endograft Device-related Complicationsmentioning
confidence: 99%
“…Device kinking (Fig. 14 ) can be localized at stent-graft limb and is defined as a sharp localized angulation > 90° on radiological examination [ 50 , 51 ]. Kinking can lead to device migration, type I and type III EL , endograft thrombosis and occlusion [ 49 ].…”
Section: Endograft Device-related Complicationsmentioning
confidence: 99%